Exploring changes in guest preferences for Airbnb accommodation with different levels of sharing and prices: Using structural topic model - Ding, Kai; Choo, Wei Chong; Ng, Keng Yap; Zhang, Qing (Frontiers in Psychology, 2023)
Online reviews have become an important source of information for investigating customers’ consumption experiences in academic studies. In the context of sharing economy-based accommodation, various studies have been conducted to investigate the user experience of Airbnb by analyzing online reviews; however, most previous Airbnb studies have focused on analyzing the user experience of Airbnb at a holistic level without distinguishing the accommodation attributes of Airbnb. Therefore, this paper aims to investigate how the preferences revealed by Airbnb users in online reviews vary across Airbnb listings with different levels of sharing and price ranges. This study analyzed 181,190 online reviews under Airbnb listings in Kuala Lumpur, Malaysia, using the Structural Topic Model (STM) and extracted 21 topics related to Airbnb service and product attributes. The findings show that Airbnb users who stay at entire property are more concerned with the hedonic value of their stay, while those who stay at shared property are more concerned with the utilitarian value. The purposes of the host-guest interaction were also found to differ in these two types of Airbnb accommodations. Regarding the effect of listing prices on users’ preferences, findings reveal that those staying at lower-priced rooms were more concerned about the convenience of exploring the surrounding area, while those who stayed in higher-priced rooms were more concerned about the surrounding environment and the interior facilities of the property.